2019
DOI: 10.22159/ijap.2019.v11s6.33572
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cox-2 Expression by Lunasin-Rich Soybean Extract on Colorectal Cancer

Abstract: Objective: The incidence of colorectal cancer has been growing faster than most other cancers in the past decade, especially in developing countries. One of the substances that is currently being investigated as potential chemopreventive agent is lunasin, which is contained in soybeans. This research explored the effect of lunasin on COX-2 expression in the distal colons of mice in which colorectal carcinogenesis was induced with azoxymethane (AOM) and dextran sodium sulfate (DSS). Methods: A total of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[91] Concurrently, classical ER signaling is tied to cell growth, proliferation, and wound healing, [92] where gastric damage models show score improvement after administration of estradiol via ER𝛼 and ER𝛽. [93] Other soy-derived fractions like lunasin reduce inflammation, histopathologic parameters, and COX-2 expression, [94] and prevent LPS-induced inflammation. [95] Lunasin can pass through the intestinal barrier intact [96] and is found rapidly in the sera of healthy male subjects after ingestion of soy protein, [97] Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[91] Concurrently, classical ER signaling is tied to cell growth, proliferation, and wound healing, [92] where gastric damage models show score improvement after administration of estradiol via ER𝛼 and ER𝛽. [93] Other soy-derived fractions like lunasin reduce inflammation, histopathologic parameters, and COX-2 expression, [94] and prevent LPS-induced inflammation. [95] Lunasin can pass through the intestinal barrier intact [96] and is found rapidly in the sera of healthy male subjects after ingestion of soy protein, [97] Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Other soy‐derived fractions like lunasin reduce inflammation, histopathologic parameters, and COX‐2 expression, [ 94 ] and prevent LPS‐induced inflammation. [ 95 ] Lunasin can pass through the intestinal barrier intact [ 96 ] and is found rapidly in the sera of healthy male subjects after ingestion of soy protein, [ 97 ] suggesting that a systemic effect is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean is also known as golden beans [3]. Soybean also contains lunasin, a polypeptide that can inhibit the expression of COX-2 enzyme in cryptic epithelial cells of the distal colon in mice that have been induced with carcinogen [4]. Soybean extract combined with probiotics significantly improves women's climacteric symptoms and sexuality [5].…”
Section: Introductionmentioning
confidence: 99%
“…[ 17–20 ] Indeed, it has been recently suggested that a lunasin‐enriched soybean extract may reduce the histopathological inflammatory index and the expression of cyclooxygenase (COX)‐2 in murine models of dextran sodium sulfate induced colitis. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%